Mentawai Language Variations in the Mentawai Islands Regency, West Sumatra Province - Satwiko Budiono; Rita Novita; Tengku Syarfina (Masyarakat Linguistik Indonesia Universitas Andalas, 2023)
The language aspect in cultural preservation focuses more on the arts and social systems. In fact, language as a connecting medium for arts and social systems also needs to be preserved. In this regard, this study seeks to language use documentation of the Mentawai language in the Mentawai Islands Regency, specifically in dialect varieties. It is intended to find out the situation and condition of the language, make language maps, and determine the varieties of the Mentawai language in the Mentawai Islands Regency. The research data were taken from 200 Swadesh’s basic vocabularies and 200 cultural vocabularies by means of direct interviews. Comparison of research data is based on seven observation areas, namely Mongan Poula, Maileppet, Muntei, Madobag, Sioban, Matobe, and Makalo villages. This study uses a dialectological approach with quantitative and qualitative methods. In this case, the quantitative method is in the form of dialectometric calculations, while the qualitative method is a description of the situation and conditions of the Mentawai language according to the language map. As a result, the Mentawai language in the Mentawai Islands Regency has two dialects, namely, the Sipora Pagai dialect and Siberut dialect. All two have a dialectometric percentage of 51—80%.